Experimental and numerical study of eccentrically loaded UHPFRC slender columns - Ahmed M. Yousef; Hamed S. Askar; Nada O. Halawa (Results in Engineering, 2025)
This study investigates experimentally and numerically the behavior of slender Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) columns under eccentric axial load. The experimental results were compared with the provisions of ACI 318-19, EC-2, and ECP-203-2020 to assess the existing code design requirements when applied to slender UHPFRC columns. The test program included nine slender columns with slenderness ratios λi of 66.67 and 55.56. The key parameters examined were the longitudinal reinforcement ratio ρl, the transverse reinforcement ratio ρst, and the end eccentricity of the applied load e/t. The experimental results indicated that the load-carrying capacity of UHPFRC slender columns that were subjected to a small eccentric load (e/t=0.2) experienced a reduction of 53.31% and that subjected to a big eccentric load (e/t=0.5) experienced about 70.17% reduction when compared with the reference axially loaded column. Increasing the ρl ratio from 2.01% to 4.52% significantly enhanced the load carrying capacity of UHPFRC slender columns by 22.89% for (e/t=0.2) and 20.79% for (e/t=0.5). Increasing the ρst ratio for specimens with e/t=0.2 from 0.49% to 1.31% led to a very slight increase in load capacity of 1.81%. The design equations for slender columns in EC-2 and ECP-202-2020 can be safely applied to UHPFRC slender columns. The moment magnification method used in ACI 318-19 generally overestimates the predictions of 2nd-order moments for slender UHPFRC columns. Based on the results, the ACI stiffness reduction factor used in calculating δns is proposed to be 0.90, and the the 2nd order moments limit in ACI may be increased to be (2.5Mu) when applied to eccentrically loaded slender UHPFRC columns. The proposed 3D numerical model showed accurate predictions of the behavior and failure modes of UHPFRC slender columns under both concentric and eccentric axial loads.